PENGARUH MODEL PEMBELAJARAN INKUIRI TERHADAP KEMAMPUAN BERFIKIR KRITIS SISWA PADA PEMBELAJARAN IPAS - Puspita Sari, Indah; Rahma Ayu, Marisa; Yanti, Cinta; Hakim, Lukman; Utomo, Budi; Kesumawati, Nila (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to determine the effect of the inquiry learning model on students' critical thinking skills in the subject of science with the material of the digestive process in humans in class V of SD Negeri 74 Palembang in the 2024/2025 academic year. This study uses a quantitative method with a True Experimental Design design, with a Posttest-Only Control Design form. The experimental class consisted of 30 students and the control class consisted of 31 students, selected through random sampling techniques. Data were collected through tests. The instrument test was conducted in class 6 of SD Negeri 74 Palembang with 8 questions and all questions were declared valid based on validity and reliability tests. Data analysis used an independent sample t-test. The results showed a significant increase in scores between the control class and the experimental class, with an average of 57.25 in the control class while the average score of the experimental class was 80.13. This study concludes that the application of the inquiry learning model significantly improves students' critical thinking skills in science learning in class V of SD Negeri 74 Palembang.